Food-derived compounds targeting ferroptosis for cancer therapy: from effects to mechanisms - Zhao, Jin-Wei; Zhao, Wei-Yi; Yu, Zhongyang (Frontiers in Oncology, 2025)
Ferroptosis is distinctive type programmed cell death. Tumor cells, with their higher iron levels, render them more susceptible to ferroptosis Inducing ferroptosis can activate immune cells, regulate immune evasion, and inhibit the biology activity of cancer cells. Therefore, ferroptosis-induced cancer cell death could become a promising approach for cancer treatment. Dietary compounds are an important source for drug discovery, and there has been an increasing amount of literature on food-derived ferroptosis inducers and their applications in cancer treatment. This review provides an overview of the regulatory mechanisms involved in ferroptosis, explores the mechanisms by which dietary compounds act as ferroptosis inducers, and discusses their effects on various cancers, especially by accumulating lipid ROS and overloading Fe2+, along with inhibiting GPX4 expression to promote ferroptosis in tumors. Additionally, the latest advancements in new methods for inducing ferroptosis, including the use of nanomaterials, are also summarized. Finally, the challenges and opportunities of developing dietary compounds as ferroptosis inducers are discussed, focusing on the discovery of new targets, enhancing selectivity, as well as reducing toxicity and the recurrence of side effects. As far as we know, this is the first comprehensive and systematic summary on the anticancer effects and mechanisms of food-derived ferroptosis inducers.